Reduced Porcine Islet Isolation Yield in the Presence of Hyperemic Islets - Hilling, D.E.; Rijkelijkhuizen, J.K.R.A.; Töns, H.A.M.; Marang-van de Mheen, P.J.; Merks, J.W.M.; Terpstra, O.T.; Bouwman, E. (Hormone and Metabolic Research, 2011)
When studying histological characteristics of porcine pancreata in relation to islet isolation, a remarkably high number of hyperemic islets (HIs) was encountered. The abnormalities observed in these HIs ranged from a single dilated vessel to hemorrhages extending into the surrounding exocrine tissue. The aim of the present study was to compare pancreata with and without HI on islet isolation outcomes. This study involved a histological examination of 143 purebred (74 juvenile and 69 adult) and 47 crossbred (only juvenile) porcine pancreata. Islet isolation was performed in 48 purebred adult pigs and in 25 crossbred pigs. Tissue samples were stained with Aldehyde Fuchsine. The presence of HIs was scored semi-quantitatively (HI–, HI+). We observed HIs in 48% of the purebred and in 68% of the crossbred pigs. However, only 3.3±3.1% and 3.1±4.7% of all assessed islets was hyperemic in HI+ pancreata in purebred and crossbred pigs, respectively. In both groups, significantly higher endocrine cell mass was found in the HI+ pancreata (p<0.01). When the higher endocrine cell mass was taken into account, we found significantly lower yields in the HI+ pancreata in both purebred and crossbred pigs (p=0.03 in both groups). The presence of HIs occurs frequently in porcine donor-pancreata and is associated with reduced isolation outcomes.
Keywords: hyperemic; islet isolation; islet transplantation; porcine; pancreas